2005
DOI: 10.1073/pnas.0501196102
|View full text |Cite
|
Sign up to set email alerts
|

Insights into regulation of human Schwann cell proliferation by Erk1/2 via a MEK-independent and p56Lck-dependent pathway from leprosy bacilli

Abstract: Activation of extracellular signal-regulated kinase (Erk) 1͞2, which plays a critical role in diverse cellular processes, including cell proliferation, is known to be mediated by the canonical Rafmitogen-activated protein kinase kinase (MEK) kinase cascade. Alternative MEK-independent signaling pathways for Erk1͞2 activation in mammalian cells are not known. During our studies of human primary Schwann cell response to long-term infection of Mycobacterium leprae, the causative organism of leprosy, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
78
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 34 publications
8
78
2
1
Order By: Relevance
“…To confirm the findings from experiments using CD1d ϩ transformed human Schwann cell lines, we conducted similar experiments using previously characterized human primary Schwann cells, which had been isolated from human adult peripheral nerve tissue and expanded up to 3-4 passages (22). Using fluorescence microscopy, we confirmed that IFN-␥-treated primary Schwann cells expressed CD1d in a diffuse and mostly homogenous distribution similar to that observed for MHC class I molecules (Fig.…”
Section: Activation Of Inkt T Cells By Human Primary Schwann Cellssupporting
confidence: 64%
See 1 more Smart Citation
“…To confirm the findings from experiments using CD1d ϩ transformed human Schwann cell lines, we conducted similar experiments using previously characterized human primary Schwann cells, which had been isolated from human adult peripheral nerve tissue and expanded up to 3-4 passages (22). Using fluorescence microscopy, we confirmed that IFN-␥-treated primary Schwann cells expressed CD1d in a diffuse and mostly homogenous distribution similar to that observed for MHC class I molecules (Fig.…”
Section: Activation Of Inkt T Cells By Human Primary Schwann Cellssupporting
confidence: 64%
“…Isolation, purification, and characterization of primary Schwann cells were previously described (21,22).…”
Section: Human Peripheral Nerve Tissue and Primary Human Schwann Cellsmentioning
confidence: 99%
“…Recent data have shown that, in order to adhere and activate SC, M. leprae and its glycolipid component PGL-I utilize molecules on the basal lamina and membrane of SC (e.g., laminin α2 and the neuregulin receptor Erb2, respectively). These events result in demyelination in rat SC co-cultures (Vincent et al 2000, Tapinos & Rambukkana 2005.…”
mentioning
confidence: 99%
“…Increasing efforts over the past decade to understand important early events in the interaction of M. leprae with peripheral nerves have resulted in the characterization of bacterial adhesins and receptors involved in M. leprae attachment to Schwann cells (de Melo Marques et al 2000, Rambukkana 2004, Soares de Lima et al 2005. The effects of M. leprae on myelin sheath integrity (Rambukkana et al 2002, Tapinos et al 2006) and on Schwann cell proliferation (Tapinos & Rambukkana 2005) have been investigated as well.…”
mentioning
confidence: 99%